Projekts SIA "Privātās pirmsskolas izglītības iestādes ABC" dibināšana - Bulude, Annija (Latvijas Universitāte, 2014)
Maģistra darba ideja ir veidot Privātu Pirmsskolas Izglītības Iestādi, kura īsteno pirmsskolas izglītības programmu, kura vērsta uz vispusīgu un kvalitatīvu bērna attīstību. Darba autore uzsver, ka projekta ietvaros netiek plānots dibināt bērnudārzu – minētā iestāde funkcionētu pēc vispārizglītojošo skolu darbības pamatprincipiem, t.i., pirmskolas audzēkņi tiktu atvesti uz konkrētām nodarbībām, kas parasti ilgst 2-4 stundas atkarībā no vecuma grupas, pēc tam tikt sniegta iespēja apmeklēt interešu izglītības nodarbības, ņemt dalību rotaļnodarbību grupā vai uzreiz doties mājup.

The idea of this Master’s thesis is to create a private preschool education institution (PPEI) which can implement preschool education programme that focuses on versatile and qualitative children development. The author of this work emphasizes that there is no plan to establish a kindergarten in the framework of this project; however, the mentioned institution would function according to fundamental principles of comprehensive school activities. More precisely, preschool students would be brought to specific classes that, depending on the age group, usually would last 2-4 hours, following which children would be presented with an opportunity to attend interest-related education classes and participate in educational game groups or directly go home.
Project Establishment of a company Private Preschool ABC
Keywords: Finanses un kredīts